Democratic Leadership and Its Impact on Teacher Performance - Sumardin Raupu; Deswita Maharani; Hilal Mahmud; Alauddin Alauddin (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study looks into the impact of the principal's democratic leadership style on teacher performance in junior high schools in Palopo City's Bara District. This study uses a quantitative approach with the type of research is ex-post facto. The population is all junior high school teachers in the Bara sub-district of Palopo city, totaling 134 people. Sampling was done by simple random sampling technique. The sample used was 39 teachers—data obtained through questionnaires and documentation. Furthermore, the research data were analyzed statistically using data processing, namely: Descriptive statistical analysis and inferential statistical analysis. This study found that the democratic leadership style displayed by the principal has a strong influence and significance on the performance of teachers in SMP/MTs in Bara District, Palopo City. This is because the leadership style displayed by the principal through several indicators can provide a significant enough stimulant to the teacher so that teachers' work motivation can increase adequately, which impacts the achievement of educational and learning goals in schools. This study implies the importance of the leadership style displayed by the principal in building teacher motivation and commitment in schools to generate optimal teacher performance in schools.